2020
DOI: 10.3389/fimmu.2020.02112
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Proteomics Identifying Novel Biomarkers for the Diagnosis of Adult-Onset Still’s Disease

Abstract: Adult-onset Still's disease (AOSD) is a systemic, multigenic autoinflammatory disease, and the diagnosis of AOSD must rule out neoplasms, infections, and other autoimmune diseases. Development of a rapid and efficient but non-invasive diagnosis method is urgently needed for improving AOSD therapy. In this study, we first performed a urinary proteomic study using isobaric tags for relative and absolute quantification (iTRAQ) labeling combined with liquid chromatography-tandem mass spectrometry analysis in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…As already demonstrated elsewhere (32), cells in whole blood remained comparably unresponsive to recombinant IL-1β, likely due to blockade or decoy of IL-1β by endogenous IL-1Ra and IL-1R2, respectively. Studies in context with other in ammatory conditions such as on Adultonset Still's Disease (AOSD) (33) or Crohn's Disease (34) similarly suggest an association of IL-1β and LRG1 expression. In contrast, studies linking LRG1 with IL-6 or TNF signaling report rather contradictory results (33,35,36), which are thus partly in line (34,35) with the weak associations observed among our KD data.…”
Section: Discussionmentioning
confidence: 97%
“…As already demonstrated elsewhere (32), cells in whole blood remained comparably unresponsive to recombinant IL-1β, likely due to blockade or decoy of IL-1β by endogenous IL-1Ra and IL-1R2, respectively. Studies in context with other in ammatory conditions such as on Adultonset Still's Disease (AOSD) (33) or Crohn's Disease (34) similarly suggest an association of IL-1β and LRG1 expression. In contrast, studies linking LRG1 with IL-6 or TNF signaling report rather contradictory results (33,35,36), which are thus partly in line (34,35) with the weak associations observed among our KD data.…”
Section: Discussionmentioning
confidence: 97%
“…Besides, collecting urine samples is more convenient and causes less pain in patients than while collecting blood samples. We previously reported a study in adult-onset Still’s disease (AOSD) and found that urine α-1-acid glycoprotein 1 (LRG1), orosomucoid 1 (ORM1), and ORM2 might be new biomarkers of AOSD ( 11 ). Similarly, in this study, we analyzed urine proteomics to identify new biomarkers that might help differentiate TAPS from OAPS.…”
Section: Discussionmentioning
confidence: 99%
“…All the patients recruited in our study were treatment-naïve, without receiving any anticoagulant therapy. Proteomics analysis was performed by protocol as previously used by our group to identify differentially expressed proteins in the urine ( 11 ). In the validation cohort, urine samples of 19 patients with primary OAPS, 21 patients with primary TAPS, 13 HCs with positive aPL antibodies (APL carriers), 20 patients with miscarriages (non-autoimmune), 21 patients with thrombosis (non-autoimmune), 30 patients with SLE, 30 patients with RA and 30 HCs were tested by enzyme-linked immunosorbent assay (ELISA).…”
Section: Methodsmentioning
confidence: 99%
“…However, no exact and reliable criteria exist yet. We define AOSD disease clinically active or inactive based on our understanding of this disease in our clinical work (34,35,(44)(45)(46)(47). Grouping AOSD disease activity status by our method was somewhat arbitrary and divergent, so it may cause the results to be biased with other research units.…”
Section: Discussionmentioning
confidence: 99%